Предмет: Алгебра,
автор: martamilaz
(x+y+z)(x-y-z) какую формулу можно применить?
Ответы
Автор ответа:
3
(x + y + z)(x - y - z) = (x + (y + z))(x - (y + z)) = x² - (y + z)² = x² - y² - 2yz - z²;
Сначала применили формулу разности квадратов:
(a - b)(a + b) = a² - b², а затем - формулу квадрата суммы:
(a + b)² = a² + 2ab + b².
Похожие вопросы
Предмет: Литература,
автор: gaipovamadina
Предмет: Математика,
автор: Aniya2773
Предмет: Алгебра,
автор: maraa077jdje
Предмет: Биология,
автор: Анна2244
Предмет: Математика,
автор: Лин77